Wearable optical device for the visually impaired in the classroom - Borges, André Fiel (2020)
Low vision is characterized by visual impairment even after treatment or medical correction, causing a number of impacts on the life of individuals. Thus, the use of assistive devices is essential to mitigate the effects of visual loss. Most of the different optical devices currently available are costly, which hinders their acquisition. The present study aimed at creating a wearable optical device for low vision, using low-cost 3D impression technologies. This is a descriptive experimental study, divided into 7 stages: ideation and creation, 3D modeling, 3D printing of structural parts, development of an original application, assembly, tests and calibration. During the first 3 stages, we created a head support onto which a smartphone could be attached as well as an image transmission and capturing module. Next, an application was developed to send the module images to the smartphone. Finally, the ensemble was calibrated with the help of a volunteer with low vision. A functional wearable optical device was developed in the form of an MVP (minimum viable product), which underwent tests and a number of functionality adjustments. The study resulted in the creation of an MVP that will be perfected through industrial modifications. However, the authors of this study are in the process of validating the device for use in subjects with low vision.